Fittability and Appearance of Brassiere Taking into Account Individual's Verge Line of Bust in Pattern Making (Journal of Fiber Bioengineering and Informatics, 2014)
To investigate the effect of the verge line on the appearance of brassieres, the difference in the verge linesof individuals with the same brassiere size was examined. A new method for designing a brassiere wasproposed, taking into account the individual's verge line using a computerised pattern-making system.Three different brassieres were made by changing the verge line of three dummy models (nine differentbrassieres in total). It was found that the verge line of the bust could differ even for the same bust size.Brassiere patterns and brassieres were made using the proposed design method and it was found thatthe verge line affected the bust cup shape and the appearance of the brassiere.